Evaluation of plasma antimicrobial peptide LL-37 and nuclear factor-kappaB levels in stable chronic obstructive pulmonary disease - Uysal, Pelin; Simsek, Gonul; Durmus, Sinem; Sozer, Volkan; Aksan, Hulya; Yurt, Sibel; Cuhadaroglu, Caglar; Kosar, Filiz; Gelisgen, Remise; Uzun, Hafize (DOVE MEDICAL PRESS LTD, 2019)
Background: Antimicrobial peptides are effectors of host defence against infection and inflammation and can encourage wound repair. Objectives: The objectives of this study were to investigate the plasma antimicrobial peptide LL-37 and nuclear factor-kappaB (NF-kappa B) levels in patients with stable COPD compared with a control group and to highlight their importance in immune inflammation. Methods: One hundred and thirty-eight stable COPD patients and 33 control subjects were enrolled in the study. The COPD patients were classified into four groups based on FEV1 (groups I-IV) and also divided into low-risk and high-risk groups (groups A-B [low risk], C-D [high risk]). Results: Plasma LL-37 levels were significantly lower while plasma NF-kappa B levels of the COPD patients were significantly higher than those of the control subjects (P<0.001, both). LL-37 levels were significantly lower in group IV than in groups I, II, and III (P<0.01, all). NF-kappa B levels were significantly higher in groups III and IV than in groups I and II (P<0.05, both). There was a positive correlation between FEV1 and FEV1/FVC in all COPD patients (r=0.742, P<0.001) and in group D (r=0.741, P<0.001). Furthermore, there was an inverse correlation between LL-37 and NF-kappa B in both the groups C (r=-0.566, P<0.001) and D (r=-0.694, P<0.001) and group C+ D combined (r=-0.593, P<0.001). Furthermore, in group C, LL-37 and FEV1 were positively correlated (r=0.633, P<0.001). Conclusion: Our study indicated that plasma LL-37 and NF-kappa B may play an important role in chronic immune inflammation. Decreased LL-37 levels may be particularly high risk for patients in stage IV disease. The role of LL-37 as a target for treatment of the immune system and COPD must be widely evaluated.
Keywords: COPD; inflammation; antimicrobial peptide LL-37; nuclear factor kappaB; CATHELICIDIN LL-37; INDUCED SPUTUM; SERUM; PROTEIN; Respiratory System